Post-Earnings-Announcement Drift and the Return Predictability of Earnings Levels: One Effect or Two? - Kausar, Asad (Management Science, 2018)
This paper examines whether earnings levels predict future returns distinct from earnings changes. I find that the predictive ability of earnings levels is subsumed by and is not incremental to the predictive ability of earnings changes. Specifically, I find that trading strategies based on net income, operating profitability, and gross profitability do not earn significant abnormal returns after controlling for earnings changes. My evidence suggests that these anomalies are an artifact of post-earnings-announcement drift and the failure to properly control for earnings changes. Data are available at https://doi.org/10.1287/mnsc.2017.2838 . This paper was accepted by Mary Barth, accounting.